The Readiness and Constraints of Technological Integration in Implementing the Case Method and Team-Based Projects in the Mechanics Course - Taufiq, Muhamad; Kaniawati, Ida; Liliasari, Liliasari; Kulthida Nugultham; Hyung-Yong Park (Universitas Negeri Semarang, 2024)
The case method and team-based projects in the mechanics course are designed to help science teacher candidates master the principles of mechanics. This study aims to analyze the readiness and constraints of technological integration in implementing the case method and team-based projects in the mechanics course of the natural science education program. The study was conducted using a survey method with respondents or samples consisting of two lecturers teaching the mechanics course, 64 pre-service science teachers, and an analysis of the mechanics course documents in the Science Education Study Program at a state university in Central Java, Indonesia. Data collection techniques for this study were carried out using a blended approach (online and face-to-face), a Google Forms questionnaire, online interviews (zoom meeting), and document review. Data analysis was carried out using the triangulation method, which combines various predetermined data and sources, including data from the mechanics course lecturers and students and the lecture tool documents. The results indicate that the readiness for implementing the case method and team-based project in the mechanics course is supported by a good understanding from lecturers and students and adequate resources. The student’s understanding of the approaches used by the lecturer obtained concept approach (71.40%), direct instruction model (85.70%), and discussion method (78.60%). In its implementation, the case method follows the theory and expectations in the mechanics lectures in the curriculum documents. Meanwhile, team-based projects still need improvement and development in their application to the mechanics course. The skills trained in the mechanics course are still limited to critical thinking skills, communication, and collaboration. Generic science skills have been trained but have not been specifically labeled, and creative thinking skills have not been technically facilitated to be trained. The carrying capacity of the learning environment is quite good based on ICT. However, it is still dominated by PowerPoint presentations and virtual lab applications, while coding blocks and AR-VR have not yet been developed. The conclusion indicates that while there is strong readiness and adequate resources for implementing the case method and team-based projects in the mechanics course, significant constraints exist in developing creative thinking skills, generic science skills, and consistency in applying learning models. Specific improvements are needed in the practical application of team-based projects and the integration of ICT that can assist mechanics lectures, such as coding blocks and AR-VR technology. It is recommended to enhance comprehension of the case method and team-based projects among lecturers and students and to advance technological integration, especially focusing on AR-VR and coding blocks.